Kualitas Pelayanan Pencatatan Masjid Berbasis Teknologi Informasi Pada Kantor Urusan Agama Kecamatan Pahandut Kota Palangka Raya - Nicodemus Nicodemus; Budy Fitri Effendi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The research discusses the quality of the mosque's recording services based on the information technology in the district of Pahandut, Palangka Raya. More specifically the purpose of this research is 1) to know the implementation of public services in the registration of mosque-based information technology in the district of the KUA Pahandut City Palangka Raya 2) to describe and analyze the quality of Public service in the mosque's registration of information technology at the KUA district of Pahandut City Palangka Raya 3) to know any obstacles that preclude the application of the mosque service based on information technology in KUA District The city of Palangka Raya. This research uses qualitative descriptive approaches. Qualitative research is a research procedure that generates descriptive data of written or spoken words from people and behaviors that can be observed. Being descriptive in this study, analysis of information is not out of the materials that are researched that is the material of the field such as the results of interviews, observation or documentation in-depth to be able to get valid data. The results of the study showed that: 1) the implementation of information technology-based mosque in KUA subdistrict of Pahandut City Palangka Raya does not suffer significant problems 2) seen in terms of physical evidence, reliability, responsiveness, assurance and empathy, KUA district of Pahandut City Palangka Raya has a diversity of problems in it 3) there are also barriers in the implementation of the registration services mosque-based information technology among others from the aspect of resources Public awareness and facilities and infrastructure.